2013
DOI: 10.2224/sbp.2013.41.10.1681
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Students' Perceptions of Assessment Tasks on Self-Eefficacy and Perception of Task Value: A Path Analysis

Abstract: Using path analysis, we examined the direct effects of students' perceptions of assessment tasks on self-efficacy, and the indirect effects through the students' perception of task value. Data were collected from 2,137 school students in Oman. Their perceptions in terms of congruence with planned learning, authenticity, student consultation, transparency, and diversity were measured using Alkharusi's (2013) Arabic version of Dorman and Knightley's (2006) Perceptions of Assessment Tasks Inventory. Task value an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
1
10
0
4
Order By: Relevance
“…Much research on self-efficacy refers back to Bandura's original definition and work (e.g., Alkharusi, Aldhafri, & Alnabhani, 2013;Tang & Tseng, 2013;van Dinther, Dochy, Segers, & Braeken, 2014). García Duncan and McKeachie (2005) offered a definition of selfefficacy that incorporated "expectancy for success (which is specific to task performance) and judgments of one's ability to accomplish a task and confidence in one's skills to perform a task" (p. 119).…”
Section: Self-efficacymentioning
confidence: 99%
“…Much research on self-efficacy refers back to Bandura's original definition and work (e.g., Alkharusi, Aldhafri, & Alnabhani, 2013;Tang & Tseng, 2013;van Dinther, Dochy, Segers, & Braeken, 2014). García Duncan and McKeachie (2005) offered a definition of selfefficacy that incorporated "expectancy for success (which is specific to task performance) and judgments of one's ability to accomplish a task and confidence in one's skills to perform a task" (p. 119).…”
Section: Self-efficacymentioning
confidence: 99%
“…In addition, congruence with planned learning, student consultation, and transparency were significantly associated with students' academic achievement whereas authenticity and diversity did not contribute significantly to the variance explained in academic achievement. In another study, Alkharusi et al (2013a) found that students' perceptions of assessment tasks had direct and indirect effects on academic self-efficacy and perceptions of task value. Alkharusi et al (2013a) concluded that teachers should develop assessment tasks in ways that activate students' sense of efficacy to accomplish the tasks and enhance their value of engaging in the tasks.…”
Section: Introductionmentioning
confidence: 96%
“…In another study, Alkharusi et al (2013a) found that students' perceptions of assessment tasks had direct and indirect effects on academic self-efficacy and perceptions of task value. Alkharusi et al (2013a) concluded that teachers should develop assessment tasks in ways that activate students' sense of efficacy to accomplish the tasks and enhance their value of engaging in the tasks. Likewise, van Dinther, Dochy, Segers, and Braeken (2014) asserted that students' perceptions of assessment can be enhanced by requiring students to do real-life tasks and giving them informative feedback, which are likely to foster their self-efficacy.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, high degrees of perceived task authenticity, transparency, diversity were associated with a high emphasis on deep learning approaches whereas a low degree of perceived task authenticity was associated with a high emphasis on surface learning approaches. Furthermore, Alkharusi et al (2013aAlkharusi et al ( , 2014a demonstrated that students' perceptions of assessment tasks had both direct and indirect effects on selfefficacy and their perceptions of task importance, interest, and utility. Recently, Alkharusi and Al-Hosni (2015) revealed that students' perceptions of assessment tasks tend to vary as a function of gender, subject area, and grade level.…”
Section: Introductionmentioning
confidence: 99%